The impact of electricity from renewable and non-renewable sources on energy poverty and greenhouse gas emissions (GHGs): Empirical evidence and policy implications. (1st June 2023) - Kocak, Emrah; Ulug, Eyup Emre; Oralhan, Burcu
Abstract: Energy poverty and greenhouse gas emissions (GHGs) are two major challenges on the road to sustainable development goals. The main goal of the global policy is to combat GHGs and energy poverty through the transition from fossil fuels to clean and renewable sources. Empirical research with a global or regional focus can offer practical implications for the development of global energy and environmental policies. To this end, this paper estimates the impact of electricity from different sources on energy poverty and GHGs in low-, middle- and high-income countries with annual data. The paper firstly performs the generalized method of moments and the sequential estimation of a linear panel-data model. According to the findings, (i) electricity from coal contributes to the increase in GHGs in the upper-middle income countries but does not have a significant effect on energy poverty. (ii) The effect of electricity from natural gas and nuclear energy on GHGs and energy poverty is mixed. Electricity from nuclear power is confirmed to have a reducing effect on energy poverty in middle and low-income countries. However, it does not have a significant effect in high-income countries. (iii) Electricity from renewable and hydro sources makes a significant contribution to reducing GHGs and energy poverty. (iv) Finally, heterogeneous estimates for robustness check greatly support baseline findings. Highlights: Examines the impact of electricity from renewable and non-renewable sources on energy poverty and GHGs in 92 countries. GMM and SELPDM dynamic panel data estimators are employed. Electricity from coal is an unsustainable option in tackling energy poverty and GHGs. The effects of electricity from nuclear and natural gas are controversial. Electricity from renewable sources is an option that supports Win-Win status.